International human rights law beyond state territorial control - Berkes, Antal (Cambridge, United Kingdom ; New York, NY : Cambridge University Press, 2021)
Can international human rights law be applied and enforced in a part of a State's territory outside its effective control? This study provides a step by step analysis to show how it can. International human rights law can normalise an imperfect, defective situation through pragmatic interpretation; it imposes obligations both on the territorial State on account of its sovereign title and residual effectiveness on the one hand, and on any subject of international law exercising territorial control over the area on account of its effective control on the other. By considering effectiveness beyond formal normative sources and titles of the subjects implicated in the territorial situation, international human rights law is interpreted and applied in a manner which renders human rights practical and effective. The book provides a comprehensive analysis of State practice regarding various subjects implicated in the territorial situation, applicable legal sources and major geographic areas.
Introduction -- The legal effect of effective control over territory -- The human rights obligations of states -- The human rights obligations of non-state actors -- The responsibility of non-state actors -- Judicial control mechanisms -- Non-judicial control mechanisms -- General conclusion.
Title from publisher's bibliographic system (viewed on 18 Jun 2021).
Keywords: Humanitarian law; Non-state actors (International relations); De facto doctrine; Military occupation